Percepção dos pescadores artesanais com o advento do canal da piracema sobre a atividade pesqueira em Guaíra, alto rio Paraná, Brasil - Silva Júnior, Lauro Ramos (2012)
The present work constitutes the study of the profile of fishermen region of Ilha Grande, upper Paraná River, composed of interviews recorded during the year 2011, collected in the islands where they reside or conduct their activities. The initial hypothesis addressed in this work is that the construction of the spawning channel system (fish passage of Itaipu Hydroelectric Power Plant), contributed positively to the diversity of fish caught in the river stretch upstream of the reservoir. The canal prompted the reappearance of some migratory species, contributing to the composition of household income, given its high market value especially gold (S. brasiliensis) and painted (P. corruscans). Included in this study the socio-economic profile of guairense fishery, and listed the elements that make up your income, your perception about the changes that have occurred in the natural environment and the way it organizes and sui generis program activities economics. To better understanding of the figure of the fishery / islet is made of contextualization universe in which it is inserted, where they described the elements of the environment, the tools, the practice of fishing. In the results it was found that the average monthly income of fishery, is 1.29 times the minimum wage, while 63.16% are focused exclusively on fishing, fishing effort is exerted for a period ranging 4-6 days and after the impoundment, the armed is became the economic base of families. In the perception of the fishery of the spawning channel, positive influence on species diversity, although the success of recruitment of fish is also linked to the flooding regime.